Integration Between Mental Health-Care Providers and Traditional Spiritual Healers: Contextualising Islam in the Twenty-First Century - Chowdhury, Nayeefa (Journal of religion and health, 2016)
In the United Arab Emirates, neuropsychiatric disorders are estimated to contribute to one-fifth of the global burden of disease. Studies show that the UAE citizens’ apathy towards seeking professional mental health services is associated with the ‘religious viewpoints’ on the issue, societal stigma, lack of awareness of mental health and lack of confidence in mental health-care providers. Mental health expenditures by the UAE government health ministry are not available exclusively. The majority of primary health-care doctors and nurses have not received official in-service training on mental health within the last 5 years. Efforts are to be made at deconstructing the position of mental illness and its treatments in the light of Islamic Jurisprudence; drafting culturally sensitive and relevant models of mental health care for Emirati citizens; liaising between Imams of mosques and professional mental health service providers; launching small-scale pilot programs in collaboration with specialist institutions; facilitating mentoring in line with Science, Technology, Engineering and Math (STEM) outreach programmes for senior school Emirati students concerning mental health; and promoting mental health awareness in the wider community through participation in events open to public.